Gas Sensors: CdS/ZnO Core/Shell Nanowire‐Built Films for Enhanced Photodetecting and Optoelectronic Gas‐Sensing Applications (Advanced Optical Materials 8/2014). Issue 8 (August 2014) - Yang, Zheng; Guo, Linjuan; Zu, Baiyi; Guo, Yanan; Xu, Tao; Dou, Xincun
<x xml:space="preserve">Abstract</x> A photodetector and a room temperature optoelectronic gas sensor with excellent performance are realized by B. Y. Zu, X. C. Dou, and co‐workers, who hydrothermally synthesize CdS/ZnO core/shell nanowires using a two‐step process on page 738. Remarkable improvement in the gas‐sensing performance under light illumination is attributed to the huge increase in photoelectron density in ZnO shell and the effective inhibition of the recombination of photogenerated electrons and holes. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>